The Poverty Impact of Rural Roads: Evidence from Bangladesh - Khandker, Shahidur R.; Bakht, Zaid; Koolwal, Gayatri B. (2012)
A rationale for public investment in rural roads is that households can better exploit agricultural and nonagricultural opportunities to employ labor and capital more efficiently. Significant knowledge gaps persist, however, as to how opportunities provided by roads actually filter back into household outcomes as well as distributional consequences. This study examines the impacts of two rural road-paving projects in Bangladesh using a new quasi-experimental household panel data set surveying project and control villages before and after program implementation. A household panel fixed-effects methodology controlling for initial area conditions is used to estimate the impact of paved roads on household and individual outcomes and account for potential bias in program placement at the village level. Rural road investments are found to reduce poverty significantly through higher agricultural production, lower input and transportation costs, and higher agricultural output prices at local village markets. Rural road development has also led to higher secondary schooling enrollment for boys and girls, as compared to primary school enrollment. We find that road investments have also benefited the poor, meaning the gains are significant for the poor and in some cases disproportionately higher than for the nonpoor.